Motion Planning of Kinematically Redundant 12-tetrahedral Rolling Robot. (11th February 2016) - Wang, Xingbo; Wang, Xiaotao; Zhang, Zhongpeng; Zhao, Ying
The 12-tetrahedral robot is an addressable reconfigurable technology (ART)-based variable geometry truss mechanism with 26 extensible struts and nine nodes arranged in a tetrahedral mesh. The robot has the capability of configuring its shape to adapt to environmental requirements, which makes it suitable for space exploration. This paper considers the motion planning problem for the robot in terms of gait planning and trajectory planning. First, a gait planning method is developed that limits the forward falling angles to only 25 degrees. Then, according to the given gait, the jerk-bounded method and inverse kinematics are utilized to calculate the trajectories of the nodes and the struts, respectively. A robot system model was built in ADAMS and simulations were conducted to demonstrate the feasibility of the motion planning method.